Comparative study on the bonding property of laser and reflow soldered Sn-3.0Ag-0.5Cu/Ni–P microbumps after isothermal aging and multiple reflowing - Yang Wu; Zhijie Zhang; Leida Chen; Shuye Zhang (Journal of Materials Research and Technology, 2024)
Laser soldering has attracted attention in microbumps joining field due to its noncontact and localized heating, a short joining time, fluxless and easy automation. In this study, Sn-3.0Ag-0.5Cu/Ni–P microbumps were prepared by laser soldering and reflow soldering respectively, then the effects of isothermal aging and multiple reflowing on microstructure and shear properties of the microbumps were compared and analyzed. The results show that a small granular and loose (Cu, Ni)6Sn5 intermetallic compounds and striated Sn grains were formed in laser-soldered microbumps, while a long and needlelike (Cu, Ni)6Sn5 intermetallic compounds and intertwined twins Sn grains were generated in reflow-soldered microbumps. During isothermal aging at 150 °C, the morphology of (Cu, Ni)6Sn5 particles changed to scallop with a large aspect ratio in the laser-soldered microbumps, which evolve to short rod-like in reflow-soldered microbumps, and the IMCs thickness in laser-soldered microbumps was always much thinner than that in reflow-soldered microbumps. The shear strength of as-soldered microbumps by laser soldering was slightly higher than that by reflow soldering ones, which sharply decreased from 0 to 100 h for both cases, and then was maintained at a similar level with increasing aging time. During multiple reflowing, the thickness of IMCs gradually increased in both cases, and the morphology of (Cu, Ni)6Sn5 particles changed to a dense short rod in laser soldered microbumps, which evolved to an irregular lumpy and long rod-like in reflow soldered microbumps. The shear strength for both laser and reflow soldered microbumps decreased with increasing reflowing times, but the decrease amplitude was all small. Moreover, the (Cu, Ni)6Sn5 IMCs transformed from granular to rod-like related to the content Ni atoms, and which critical value was evaluated to be 6–10 at%, based on the Jackson parameter α. Therefore, laser soldering is effective for reducing the thickness of IMCs and ensuring the mechanical property after isothermal aging and multiple reflowing of the microbumps was similar to reflow soldering.